Istota i charakter gminnych problemów rozwojowych - diagnoza stanu obecnego w świetle badań empirycznych - Ignacy, Jarosław; Kopyściański, Tomasz (The Essence and Character of Local Development Problems - Current State Diagnosis Based on Empirical Research, 2008)
Some conclusions gathered during holistic empirical research of Lower Silesian communities are presented in this article. Communal self-government has substantially increased its role since 1989. Although new chances and opportunities have been given, many new threats and problems had to be faced up. Local development is the most important aim of communal self-government. This paper describes the main problems, regarding the process of local development, that the local communities are dealing with. It also indicates its main causes of observed difficulties. The current state analysis is based on an empirical approach.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 97-105